(untitled) (Homoeopathy for All, 2025)
Objective: This study aims to compare and analyse various schools of homeopathy, exploring their methodologies, benefits, limitations, and their alignment with or departure from Samuel Hahnemann’s original principles. The objective is to provide a comprehensive understanding of these schools, highlighting the evolving landscape of homeopathic practice. Methods: The study systematically examines traditional and modern homeopathic schools, focusing on their unique approaches to treatment and diagnosis. It explores the foundational Classical Homeopathy, which strictly adheres to Hahnemann’s philosophy of single remedy prescribing based on the totality of symptoms and the Vital Force, alongside more contemporary schools such as Sankaran’s Sensation Method, Bogerian Homeopathy, Scholten’s Homeopathy, Shah’s Homeopathy, and Predictive Homeopathy. Additionally, newer and unconventional methodologies, including B.S. Shashni’s Method (incorporating hair analysis) and Astro homeopathy (blending astrology with treatment), are discussed. Results: The study reveals that modern schools introduce innovative concepts, such as multiple remedy approaches, an emphasis on emotional and psychological states, and scientific frameworks (e.g., Periodic Table of Elements) that attempt to align homeopathic remedies with chemical properties. These schools provide a broader scope of treatment options but diverge from classical homeopathy in key areas like remedy selection, diagnostic tools, and the integration of non-traditional frameworks. The inclusion of unconventional methods like hair analysis and astrology further expands the boundaries of classical homeopathy, offering new diagnostic and treatment paradigms. Discussion: While Classical Homeopathy remains the most established and comprehensive method, deviations introduced by schools like Sankaran’s Sensation Method and Scholten’s Homeopathy provide valuable contemporary alternatives, incorporating psychological, emotional, and scientific elements. Bogerian Homeopathy and Shah’s Homeopathy offer a mix of constitutional and combination remedy approaches, which expand the range of treatment options for chronic and complex conditions. However, the study also identifies significant contradictions among these schools, particularly in their approach to remedy selection and the emphasis on emotional vs. physical symptoms. The balance between holistic versus scientific frameworks remains a central point of contention. Conclusion: The study concludes that Classical Homeopathy remains the most reliable and foundational method for students seeking in-depth training in homeopathy, providing a solid understanding of traditional healing principles. However, modern schools like Sankaran’s and Scholten’s introduce valuable perspectives that can complement classical practice. The Shashni’s Method and Astro homeopathy offer alternative approaches, expanding the treatment options available to patients and practitioners. A critical understanding of each school’s strengths, limitations, and contradictions is essential for making informed choices in homeopathic practice.